2014
DOI: 10.3168/jds.2014-8106
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant bovine interferon-τ enhances in vitro development of bovine embryos by upregulating expression of connexin 43 and E-cadherin

Abstract: Interferon-τ (IFNT), produced in ruminants by embryonic trophoblastic cells before implantation, is involved in the maternal recognition of pregnancy. It is a pleiotropic molecule that alters the synthesis of endometrial proteins and inhibits the proliferation of some cells. The present study investigated the effects of recombinant bovine IFNT on the development of early-stage bovine embryos and the molecular mechanism underlying this effect. This study demonstrated that expression of mRNA encoding type I IFN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…In the present study, baicalin increased Gja1 and Cdh1 gene expression in IVC embryos, which coincided with the higher blastocyst formation rates, similar to the injection of GJA1 or CDH1 double-stranded RNA into bovine zygotes decreased the percentage of zygotes developing to blastocyst by 18.4 and 16.3% in vitro , respectively [31]. It has also been reported that both CDH1 and GJA1 mRNA expression levels are positively correlated with the quality of bovine blastocysts [24]. Our results indicate that baicalin promotes in vitro development of mouse embryos by up-regulating Gja1 and Cdh1 gene expression.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, baicalin increased Gja1 and Cdh1 gene expression in IVC embryos, which coincided with the higher blastocyst formation rates, similar to the injection of GJA1 or CDH1 double-stranded RNA into bovine zygotes decreased the percentage of zygotes developing to blastocyst by 18.4 and 16.3% in vitro , respectively [31]. It has also been reported that both CDH1 and GJA1 mRNA expression levels are positively correlated with the quality of bovine blastocysts [24]. Our results indicate that baicalin promotes in vitro development of mouse embryos by up-regulating Gja1 and Cdh1 gene expression.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that the embryo quality and viability is mainly affected by in vitro culture conditions [4, 22,23,24], and high-quality embryos can be achieved through modifying culture conditions [24, 25]. Baicalin has been reported to promote embryo implantation and maintain pregnancy in mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…The expression is related to the stage of development (Barcroft et al, 1998; Shehu et al, 1996) and, in one study, expression was greater in good quality blastocysts compared to poor quality blastocysts (Sathanawongs, Nganvongpanit, & Mekchay, 2012). IFNT enhanced the development of bovine IVF embryos (Bao, Zhao, Haq, & Zeng, 2014; Zhao, Wu, Gao, Evans, & Zeng, 2017) and this was associated with upregulation of E‐cadherin and connexin 43, the latter a gap junction intercellular communication protein (Ribeiro‐Rodrigues et al, 2017). Suppression of the E‐cadherin gene and connexin 43 gene using RNA interference decreased the proportion of bovine embryos that developed to blastocysts (Nganvongpanit et al, 2006; Tesfaye et al, 2007).…”
Section: Adhesion Molecules and Reproduction In Cattlementioning
confidence: 99%
“…El número de blastómeras a los 7 días de cultivo, obtenidos en el presente trabajo fueron similares a los obtenidos por diferentes grupos de investigación que utilizaron el mismo tipo de tinción para evaluar calidad embrionaria. Bao y colaboradores, encontraron blastocistos con 116 blastómeras en su grupo control en cultivo in vitro con interferón tau 35 , mientras que Santana y colaboradores reportaron 84.6 blastó-meras para el grupo control de su experimento 36 . En este experimento se reportaron blastocistos con 101 blastómeras para COC tipo I y 104 blastómeras para los tipo II los cuales son números de blastómeras reportados como normales para blastocitos bovinos 35 .…”
Section: Discussionunclassified